Connected Through Awe: Can Interactive Virtual Reality Elicit Awe for Improved Well-Being? - Quesnel, Denise T.; Riecke, Bernhard E. (3rd Annual Innovations in Psychiatry and Behavioral Health: Virtual Reality and Behavior Change, 2017)
Experiences of awe have therapeutic, health, and educational benefits, characterized by profound feelings of social interconnectivity, shifts in perspective, and increased life satisfaction. However, awe remains a rare experience in our busy everyday lives, and rarer in lab environments. Here, we investigated how personalized VR could provide an opportunity to improve well-being through elicitation of awe. We conducted a mixed-methods study, with participants interacting with VR to visit virtual wonders of the world, and to see Earth from outer space. We complemented introspective measures and survey data reporting participants’ level of awe and wonder with physiological measures of raised goose bumps on the skin, often called ‘chills’, which are known to be a specific marker of this awe experience. 43.8% of participants experienced goose bumps, and those who experienced goose bumps showed significantly higher ratings of awe than those who did not. Participants that had personalized environments (created through self-selecting the places they visited in VR) experienced more intense awe. Participants who struggled with the interaction interface reported distraction from the virtual environment, had fewer occurrences of goose bumps, and less self-reported awe. Introspective findings of those who experienced awe revealed themes of feeling calmed by the experience, increased curiosity, and profound social connection with their home, friends, and families. These findings demonstrate: 1) Personalized environments improve elicitation of awe in VR; 2) VR interaction interfaces that minimize distraction are important for eliciting awe; 3) VR has a powerful capacity in eliciting awe for improved well-being.
Keywords: Riecke; Riecke_2017; awe; bernhard-riecke; denise-quesnel; earthgazing; poster; posterWithoutPaper; talkWithoutPaper